Twin pregnancy after kidney transplant – the insight of the prenatal and postnatal problems based on a case report - Michalak-Kloc, Marzena; Kłosowska-Kwapisz, Magdalena; Perez, Ewa Rojas; Walczak, Kornelia; Kuszerska, Agata; Malinowski, Witold (Pediatria Polska - Polish Journal of Paediatrics, 2021)
Twin pregnancy after a kidney transplant is rare and is known to be a high-risk pregnancy. Chances of getting pregnant after a kidney transplant are higher than for patients with renal chronic disease. The most common problems which can occur are: severe hypertension, preeclampsia, abruption of the placenta and fetal growth restriction. We present a case of twin pregnancy after a kidney transplant, on three immunosuppressant medications, complicated by arrhythmia treated by cardioversion, severe fetal growth restriction in twin 2, and preeclampsia. The pregnancy was ended at nearly 28 weeks of gestation due to abruption of the placenta in the normally growing twin. The birth weight was as follows: in twin 1-1200 g and in twin 2-620 g. We present problems during the postnatal period and outcomes at 12 months of life.